The nature and rate of injury in elite sport aerobics athletes - Fetterplace, J. (2004)
This study investigated the injuries sustained by elite Australian sport aerobic athletes in the 12 months prior to the FISAF world's sport aerobics championships in May/June 2004. Data was collected using a retrospective questionnaire developed from published research in similar areas. This study is important in establishing the prevalence and rate of injury in elite sport aerobic athletes and provides a basis for further research.